Commercial Diplomacy as an Instrument of Outward Foreign Direct Investment: Evidence from Indonesia’s Indomie Investment in Serbia - Yunus, Aulia Shalahuddin; Paksi, Arie Kusuma; Waluyo, Waluyo (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2025)
The evolving landscape of international economic relations underscores the strategic significance of commercial diplomacy in advancing national economic interests abroad. This study examines Indonesia’s use of commercial diplomacy to facilitate foreign direct investment (FDI) through the establishment of an Indomie instant noodle manufacturing facility in Serbia. The analysis is grounded in a commercial diplomacy framework, which conceptualizes state-led support for international business, and is complemented by Dunning’s Eclectic Paradigm (OLI) to explain the ownership, location, and internalization advantages underlying Indonesia’s outward investment strategy. Methodologically, this research employs a qualitative case study approach based on systematic analysis of secondary data, including official government documents, bilateral agreements, corporate reports, academic literature, and credible media sources. Data are examined using thematic analysis and triangulation to ensure analytical rigor and validity. The findings demonstrated that Indonesia’s FDI initiative in Serbia is driven by economic diversification objectives, the strategic deployment of national branding through Indomie, and Serbia’s locational advantages as a gateway to the European Union market. Moreover, the collaboration has generated mutual economic and political benefits, including employment creation, infrastructure development, and strengthened bilateral trade networks. This study contributes to the literature on international political economy by illustrating how commercial diplomacy, when aligned with firm-level investment strategies, can function as both a market-entry mechanism and an instrument of geopolitical engagement.